Phytochemical profiling, antioxidant potentiality and antibacterial activity of the ethanolic extracts of Rosenvingea sp. of Bay of Bengal (Journal of Bangladesh Academy of Sciences, 2021)
The objective of the present study was to explore the phytochemical profiling, antioxidant and antimicrobial activity of 50% ethanolic extract of Rosenvingea sp. found in the Bay of Bengal of Bangladesh. Seven phytochemicals were tested from the ethanolic extract of Rosenvingea, where four phytochemicals, namely steroid, glycosides, alkaloids, and tannins were present. However, ethanol extract exhibited low antioxidant activity compared to standard ascorbic acid as measured by DPPH-Free radical scavenging assay. In Brine Shrimp lethality bioassay, 50% ethanolic extract showed an LC50 value of 10.88 mg/mL, whereas positive control (K2Cr2O7) showed LC50 59.97 µg/mL suggesting the less toxic property of the ethanolic extract. In-vitro antimicrobial activity of ethanolic extract of Rosenvingea sp. was investigated against gram-positive and gram-negative bacteria species (Staphylococcus, Bacillus, Pseudomonas, Salmonella, and Klebsiella) by agar disc diffusion method. The highest antibacterial activity was noticed against Klebsiella pneumonia, Pseudomonas aeruginosa, Staphylococcus hominis with a zone of inhibition of 5.00±1.00 mm, 3.66±0.57 mm, and 3.33±0.57 mm, respectively. This is the first study on Rosenvingea sp. from the Bay of Bengal, reporting its phytochemical, antioxidant, and antimicrobial potentiality. However, more study is required to elucidate its commercial viability in the food and medicine industries.J. Bangladesh Acad. Sci. 45(1); 59-71: June 2021